Co-movement of prices of energy and agricultural commodities in biofuel era: A period-GARCH copula approach - Gong Xue (2018)
This study examines volatility and co-movement structures of coal and agricultural commodities index returns in China's bioful era. After taking into account the periodicity of changes in coal and agriculture prices, we show that the Period-GARCH (P-GARCH), which captures the characteristics of two commodities is more adequate in contrast to the previously proposed models where the residuals were skewed and had kurtosis, here the resulting residuals are almost Gaussian. Finally, our proposed P-GARCH time-varying copula models indicate that the dependence between energy and agricultural commodities index returns is positive and increasingly stable. © Springer International Publishing Switzerland 2014.